Normal serum ApoB48 and red cells vitamin E concentrations after supplementation in a novel compound heterozygous case of abetalipoproteinemia. (May 2019) - Di Filippo, Mathilde; Collardeau Frachon, Sophie; Janin, Alexandre; Rajan, Sujith; Marmontel, Oriane; Decourt, Charlotte; Rubio, Amandine; Nony, Séverine; Dumont, Sabrina; Cuerq, Charlotte; Charrière, Sybil; Moulin, Philippe; et al.
Abstract: Background and aims: Abetalipoproteinemia (ABL) is a rare recessive monogenic disease due to MTTP (microsomal triglyceride transfer protein) mutations leading to the absence of plasma apoB-containing lipoproteins. Here we characterize a new ABL case with usual clinical phenotype, hypocholesterolemia, hypotriglyceridemia but normal serum apolipoprotein B48 (apoB48) and red blood cell vitamin E concentrations. Methods: Histology and MTP activity measurements were performed on intestinal biopsies. Mutations in MTTP were identified by Sanger sequencing, quantitative digital droplet and long-range PCR. Functional consequences of the variants were studied in vitro using a minigene splicing assay, measurement of MTP activity and apoB48 secretion. Results: Intestinal steatosis and the absence of measurable lipid transfer activity in intestinal protein extract supported the diagnosis of ABL. A novel MTTP c.1868G>T variant inherited from the patient's father was identified. This variant gives rise to three mRNA transcripts: one normally spliced, found at a low frequency in intestinal biopsy, carrying the p.(Arg623Leu) missense variant, producing in vitro 65% of normal MTP activity and apoB48 secretion, and two abnormally spliced transcripts resulting in a non-functional MTP protein. Digital droplet PCR and long-range sequencing revealed a previously described c.1067+1217_1141del allele inherited from the mother, removing exon 10. Thus, the patient is compound heterozygous for two dysfunctional MTTP alleles. The p.(Arg623Leu) variant may maintain residual secretion of apoB48. Conclusions: Complex cases of primary dyslipidemia require the use of a cascade of different methodologies to establish the diagnosis in patients with non-classical biological phenotypes and provide better knowledge on the regulation of lipid metabolism. Graphical abstract: Image 1 Highlights: Clinically typical abetalipoproteinemia (ABL) proband with two MTTP mutant alleles. ABL with normal apoB48 concentration but deficient serum fat soluble vitamins. c.1868G>T undergoes abnormal splicing and infrequently p.R623L functional variant. Requirement of methods detecting heterozygous copy number variation on MTTP . Normal vitamin E in red cells in case of normal apoB48 secretion.